Monte Carlo Model in Metal Recrystallization Simulation - 张继祥 文辉 刘运腾 (Shanghai jiao tong da xue xue bao, 2011)
Some new advices are proposed for Monte Carlo model of recrystallization annealing simulation, including an additional recovery process, a new stored energy distribution, a more advanced nucleation model and a conversion probability of site orientation. Then a Monte Carlo model is established absorbing the above improvements, and used to isothermal annealing simulation of 1060 pure aluminum cold-rolled sheet. For contrast, a recrystallization annealing experiment of 1060 pure aluminum is carried out at the same time. The results show that the 1060 aluminum alloy in the annealing experiment produces obvious recrystallization, and the grain morphology of recrystallization is similar to isometric. The new model can effectively simulate the non- homogeneous nucleation process and the microstructure evolution of 1060 industrial pure aluminum in annealing, and the simulated recrystallization kinetics curve is similar to the theoretical curve. The Avrami exponent coincides with the experimental result but is lower than the theoretical value of 2. As the Monte Carlo model does not consider the preferential growth orientation, some simulated results are not completely consistent with that from experiments.